Novel Linear Piezo Actuator (R&D Journal, 2019)
This publication presents a novel concept for an electromechanical piezoelectric actuator. This concept is intended to enable a piezoelectric actuator that exceeds the current state of the art in terms of achievable deflection at operating frequencies in the range of 0 Hz to 100 Hz. This will be realised by merging the strokes of individual piezo stacks. The concept enables linear or rotational movement. The linear version will be discussed here. An actuator of this type enables high-speed positioning of, for example, shafts, valves or lasers.